STRENGTHENING RELIGIOUS ATTITUDES AND INTERFAITH COMMUNICATION IN BUILDING SOCIAL HARMONY: PEACE AND CONFLICT TRANSFORMATION - Saputra, Edy; Sutrisno, Sutrisno; Zulmaulida, Rahmy; Noviani, Julia; Gradini, Ega; Harnedi, Joni; Hikmah, Nurul; Utami, Rizka (As-Sidanah, 2025)
Indonesia's religiously plural districts have periodically experienced tensions rooted in administrative procedures and misunderstandings in interfaith relations. This service activity aimed to identify forms of religious attitudes and communication patterns in Aceh Tengah and Aceh Singkil communities, as well as surface participatory strategies for sustaining social harmony. Using a Participatory Action Research (PAR) cycle, the program included Training of Trainers (ToT), Focus Group Discussions (FGDs), participatory mapping, community education, and iterative monitoring and evaluation conducted with teachers, students, religious leaders, FKUB members, and local officials. The service showed that Aceh Tengah exhibited strong tolerance supported by inclusive Gayo cultural norms, open deliberative communication, and proactive engagement between the government and the FKUB. Aceh Singkil faced recurrent challenges related to worship-permit arrangements, yet communities maintained mutual respect and associative ties that helped de-escalate issues. The program empowered local stakeholders to act as agents of tolerance and clarified bottom-up feedback channels within existing top-down procedures, generating practical improvements and guidance for replication. In conclusion, collaborative, bottom-up communication institutionalized through government, interfaith forums, and community partnerships was essential to manage diversity and sustain harmony; the PAR-based approach provided a practical model and transferable lessons for similar plural settings across Indonesia.